Prenatal exposure to antibiotics and risk of neurodevelopmental disorders in offspring: A systematic review and meta-analysis - Tao, Qiuji; Shen, Yajun; Li, Yang; Luo, Huan; Yuan, Meng; Gan, Jing (Frontiers in Neurology, 2022)
Background and purpose A growing body of research suggests that inflammation and maternal infections may lead to an increased risk of neurodevelopmental problems such as attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), cerebral palsy (CP), and epilepsy in offspring. The aim of this study was to observe the connection between prenatal antibiotic exposure and the risk of these neurodevelopmental disorders in offspring. Patients and methods A comprehensive search was conducted in the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Google Scholar, and Scopus databases for observational studies that looked into the link between prenatal exposure to antibiotics and the risk of neurodevelopmental problems in offspring, published from 1 January 1950 to 31 January 2022. The Newcastle–Ottawa Scale (NOS) was used to assess the quality of the included studies. Data were analyzed using the STATA version 12 software, and an odds ratio (OR) with a 95% confidence interval (CI) was reported. Results A total of 15 studies were included in the meta-analysis. Prenatal antibiotic exposure was associated with the increased risk of ADHD (OR = 1.14; 95% CI = 1.13 to 1.15; I2 = 0%) and epilepsy (OR = 1.34; 95% CI = 1.02 to 1.66; I2 = 96.8%). The link between prenatal antibiotic exposure and the risk of ASD [OR = 1.09; 95 % CI = 0.88 to 1.31; I2 = 78.9%] and CP [OR = 0.99; 95% CI = 0.56 to 1.43; I2 = 91%] was found to be non-significant. In all of the included prospective cohort studies, subgroup analysis suggested a significant association between prenatal antibiotic exposure and the incidence of ASD [OR = 1.17; 95% CI = 1.03 to 1.31; I2 = 48.1%] and CP [OR = 1.18; 95% CI = 1.02 to 1.34; I2 = 0%]. Conclusion Prenatal antibiotic exposure during pregnancy is linked to a higher incidence of ADHD and epilepsy in the offspring. Further prospective studies that compare prenatal antibiotic use and are adjusted for various confounders are needed to further assess the association of prenatal antibiotic exposure and neurological disorders in offspring. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022306248.